Using high energy ruby laser to generate plasma for aluminum material (object) and study its spectrums (Latakia University Journal -Basic Sciences Series, 2018)
This research studies the principle of the work of laser sapphire and its development mechanism to obtain a high-energy pulse laser where the intensity of pulse  and intensity of its electric field  can be reached when the pulse is out of the laser. And then measure and calculate all parameters of this laser are: the length of the wave , frequency , the energy of a photon , the number of photons  of one pulse, pulse capacity , intensity of pulse  and intensity of  electric field . Hence, study the spectral lines of the plasma generated by changing the gas medium surrounding the target material, and determine the displacement constants of the resulting spectral lines. The spectral lines are then studied by varying the radiation energy density of the laser pulse used, and its relation to the absolute temperature  of the plasma.As the result of this study, the parameters widening  and shifting   of spectrum liens and the concentration of electrons  in plasma had been calculated. Finally, the relative and absolute relativities measured in measured physical quantities were calculated.